Diagnosis and treatment of reflex-pain syndromes in patients with herniated intervertebral disc before surgical decompression - Ye. B. Kolotov; A. A. Lutsik; A. V. Mironov; S. V. Yelagin (Бюллетень сибирской медицины)
To upgrade the results of surgical treatment in patients operated on for gerniated intervertebral disk the reflex-pain syndromes of spondylarthrosis and osteohondrous was studied. Before surgical treatment alcohol-novocain blockades have been used to perform denervation of intervertebral discs and joints. The reflex-pain syndromes was evoked by solution injection and then arrested by alcohol-novocain injection. Clinical outcome in long-term period after surgical treatment became good in 89% (p < 0.05) on cervical spine and in 84% (p < 0.05) lumbar.